Odpowiedzi

2009-12-04T15:16:09+01:00
1a)(a+7)=a²+14a+49
b)(1,2+b)²=1,44+2,4b+b²
c)(c+1 2/3)²=c²+3 1/3c+2 7/9
d)(√5-d)²=5-2√5d+d²
e)(3k+ 2/5)²=9k²+1 1/5+4/25
f)(5m+6n)²=25m²+60mn+36n²

2a)(z-9)²=z²-18z+81
b)(0,7-w)²=0,49-1,4w+w²
c)(u-2 1/3)²=u²-4 2/3u+ 5 4/9
d)(√3-v)²=3-v√3+v²
e)(3y-3/4)²=9y²-4,5y+9/16
f)(1,1-0,3x)²=1,21-0,66x+0,09x²
2009-12-04T15:18:28+01:00
1a)(a+7)=a²+14a+49

b)(1,2+b)²=1,44+2,4b+b²

c)(c+1 2/3)²=c²+3 1/3c+2 7/9

d)(√5-d)²=5-2√5d+d²

e)(3k+ 2/5)²=9k²+1 1/5+4/25

f)(5m+6n)²=25m²+60mn+36n²


2a)(z-9)²=z²-18z+81

b)(0,7-w)²=0,49-1,4w+w²

c)(u-2 1/3)²=u²-4 2/3u+ 5 4/9

d)(√3-v)²=3-v√3+v²

e)(3y-3/4)²=9y²-4,5y+9/16

f)(1,1-0,3x)²=1,21-0,66x+0,09x²
2009-12-04T15:24:16+01:00
(a+7)*=a*+14a+7*
(1,2+b)*=1,2*+2,4b+b*
(1c+1 2/3)*=c*+10/3c+25/9
(^5-d)*=5-10d+d*
(3k+2/5)*=9k+12/5k+4/25
(5m+6n)*=25m+60mn+36n*



(z-9)*=z*-18z+18
(0,7-w)*=0,49-1,4w+w*
(u-2 1/3)*=u*-14/3u+49/9
(^3-v)*=3-6v+v*
(3y-3/4)*=9y-18/4y+9/16
(1,1-0,3x)*=1,11-0,66x+,0,09x*